RABI'AH AL-ADAWIYAH (Riwayat Hidup dan Konsep al-Mahabbah al-Ilahiyah) - St. Aisyah Abbas; Akramun Nisa (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2022)
This article discusses the life history of Rabi'ah Al-Adawiyah and the concept of al-Mahabbah al-Ilahiyah. From the discussion, it was understood that her full name was Rabi'ah bint Ismail al-Adawiyah, she was born in Basrah in 95 H./713-714 M. died 185 H/801 M. She came from a poor family who was devoutly religious, at the age of approaching adulthood, in one incident he was captured and then sold and then made into a slave, until finally freed by his master after seeing a strange incident that happened to Rabi'ah Al-Adawiyah. No accurate data was found, Rabi'ah Al-Adawiyah had studied with a sheikh or a teacher. However, according to A. J. Arberry, he was a student of the leader of Zahid, namely Abu Sulaiman ad-Darani. Rabi'ah Al-Adawiyah chose to live her life alone, Rabi'ah Al-Adawiyah never married, even though there were at least 2 (two) people who had proposed to her for marriage. Rabi'ah Al-Adawiyah is considered the first person to declare the doctrine of unconditional love for Allah. Love speaks with longing and feelings. Only those who feel love can know what love is. As an expression of the servant's love for Allah, that love must cover other than the Beloved or the Beloved. In other words, then; 1). he had to turn his back on the world and all its attractions. 2). he must separate himself from his fellow creatures of Allah, so that he cannot attract/obstruct from the Creator.